Sosialisasi Perawat Dalam Pengisian Pendokumentasian Data Penunjang Pasien Rawat Inap Dengan Aplikasi Elektronik Rekam Medis Ruang Alexandri Lt 3 Di RSUD Dr.H.Moch Ansari Saleh Banjarmasin - Rabiatul Adawiah; Arief Budiman; Nadira Amelia Oktiana (CV. ITTC INDONESIA, 2024)
Socialization of nurses in filling in the documentation of supporting data for inpatients with an electronic application of medical records is an important step in improving efficiency and accuracy in health services. Nurses need to understand the process and usefulness of the application in order to optimize its use in daily practice. This socialization began with an understanding of the basic features of the electronic medical record application, including how to access and fill in patient data appropriately and efficiently.